Sperm DNA methylation patterns at discrete CpGs and genes involved in embryonic development are related to bull fertility - Štiavnická, Miriama; Chaulot-Talmon, Aurélie; Perrier, Jean-Philippe; Hošek, Petr; Kenny, David A; Lonergan, Patrick; Kiefer, Hélène; Fair, Sean (BMC genomics, 2022)
BACKGROUND: Despite a multifactorial approach being taken for the evaluation of bull semen quality in many animal breeding centres worldwide, reliable prediction of bull fertility is still a challenge. Recently, attention has turned to molecular mechanisms, which could uncover potential biomarkers of fertility. One of these mechanisms is DNA methylation, which together with other epigenetic mechanisms is essential for the fertilising sperm to drive normal embryo development and establish a viable pregnancy. In this study, we hypothesised that bull sperm DNA methylation patterns are related to bull fertility. We therefore investigated DNA methylation patterns from bulls used in artificial insemination with contrasting fertility scores. RESULTS: The DNA methylation patterns were obtained by reduced representative bisulphite sequencing from 10 high-fertility bulls and 10 low-fertility bulls, having average fertility scores of - 6.6 and + 6.5%, respectively (mean of the population was zero). Hierarchical clustering analysis did not distinguish bulls based on fertility but did highlight individual differences. Despite this, using stringent criteria (DNA methylation difference ≥ 35% and a q-value < 0.001), we identified 661 differently methylated cytosines (DMCs). DMCs were preferentially located in intergenic regions, introns, gene downstream regions, repetitive elements, open sea, shores and shelves of CpG islands. We also identified 10 differently methylated regions, covered by 7 unique genes (SFRP1, STXBP4, BCR, PSMG4, ARSG, ATP11A, RXRA), which are involved in spermatogenesis and early embryonic development. CONCLUSION: This study demonstrated that at specific CpG sites, sperm DNA methylation status is related to bull fertility, and identified seven differently methylated genes in sperm of subfertile bulls that may lead to altered gene expression and potentially influence embryo development.
Keywords: Cattle; Animals; skot; Female; spermie; ženské pohlaví; Spermatozoa; Epigenetics; fertilita; těhotenství; metylace DNA; Fertility; Semen Analysis; Male; RRBS; Embryonic Development; analýza spermatu; DNA Methylation; Male fertility; Dairy industry; DNA methylation; zvířata; embryonální vývoj; mužské pohlaví; Pregnancy